VD_FINDINFO Décision / 2013 / 1064 vom 24. Dezember 2013 - VD Tribunal cantonal (2013)
RISQUE DE COLLUSION, RISQUE DE FUITE, RISQUE DE RÉCIDIVE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH)